Banda de música da força policial militar do Ceará: uma história social de práticas e identidades musicais (c.1850-1930) - Inez Beatriz de Castro Martins (2017)
This work aims to investigate the music band that was constituted in the former Police Corps of Ceará, the current Military Police of Ceará, trying to understand how the musicians that constituted the band related with each other, with the institution and with the local society. In addition, it was important to perceive the musical practices incorporated and transformed over time, seeking to characterize the musical identities of this police band. The period under study begins in the decade of creation of the police band, in the year 1854, having as final mark the decade of 1930, period in which the process of militarization of the police band was consolidated and, on the other hand, the cultural life of Fortaleza has changed significantly. This thesis worked a varied set of handwritten, printed, musical, and visual sources such as musicians personal files books, local press, the band score sheet archive and photographs of the group throughout the period in question. The reason for the presence of music band within a police institution, the presence of children in the band and the existence of a symphonic orchestra representative of a Public Security institution was initially questioned from the photographic sources. The answers to these questions are directly related to the importance and influence that the police band acquired in the social and cultural life of the city of Fortaleza during the Empire and the First Republic. The frequent activity of the police group in private and public events of the city reflected a broad musical phenomenon of the military bands during the long nineteenth century. The musical practices of the military bands of the nineteenth century spread throughout several countries of Europe and in the United States, arriving also in Brazil. In addition to characteristic martial marks (parades, uniforms, colours and hierarchies), these bands had a wider cultural impact. The musical identity of the band of the Military Police Force of Ceará between 1850 and 1930 was thus observed through the study of the social profile of the musicians who formed the band, in the choice of repertoires, in the constitution of different instrumental formations and in the way of orchestrating the group's compositions.